Enterprise vocabulary management; A lexicographic view - Voskuil, Jan (Wacana, Journal of the Humanities of Indonesia, 2015)
The central theme in this paper is the problem of shifting from natural language descriptions, as in traditional dictionaries and thesauri, to working IT (Information Technology) systems that support people carrying out their administrative tasks. An explicit description of the specific language used in an organization is necessary to guarantee properly working IT systems and a healthy flow of information. Traditionally, there are different ways of capturing such a vocabulary. Different options are considered, arguing that the general form of a thesaurus offers the optimal solution for a broad range of cases. Various requirements for such a thesaurus are examined. A real world example is discussed in some detail. Finally, the paper examines how modern Web technology can help optimizing the creation, management and use of enterprise thesauri. Using these technologies, the enterprise thesaurus can take up new roles in managing the information household of an organization.